Integrated Transcriptome Analysis and Single-Base Resolution Methylomes of Watermelon (Citrullus lanatus) Reveal Epigenome Modifications in Response to Osmotic Stress - Zhu, Fangming; Li, Mingyan; Yan, Manwen; Qiao, Fei; Jiang, Xuefei (Frontiers in Plant Science, 2021)
DNA methylation plays an important role against adverse environment by reshaping transcriptional profile in plants. To better understand the molecular mechanisms of watermelon response to osmotic stress, the suspension cultured watermelon cells were treated with 100mM mannitol, and then a methylated cytosines map was generated by whole genome bisulfite sequencing (WGBS). Combined with transcriptome sequencing, the effects of osmotic stress on differentially methylated expressed genes (DMEGs) were assessed. It was found that genes related to plant hormone synthesis, signal transduction, osmoregulatory substance-related and reactive oxygen species scavenging-related enzyme could rapidly respond to osmotic stress. The overall methylation level of watermelon decreased after osmotic stress treatment, and demethylation occurred in CG, CHG, and CHH contexts. Moreover, differentially methylated expressed genes (DMEGs) were significantly enriched in RNA transport, starch and sucrose metabolism, plant hormone signal transduction and biosynthesis of secondary metabolites, especially in biosynthesis of osmolytes synthase genes. Interestingly, demethylation of a key enzyme gene Cla014489 in biosynthesis of inositol upregulated its expression and promoted accumulation of inositol, which could alleviate the inhibition of cell growth caused by osmotic stress. Meanwhile, a recombinant plasmid pET28a-Cla014489 was constructed and transferred into Escherichia coli BL21 for prokaryotic expression and the expression of ClMIPS protein could improve the tolerance of E. coli to osmotic stress. The effect of methylation level on the expression properties of inositol and its related genes was further confirmed by application of DNA methylation inhibitor 5-azacytidine. These results provide a preliminary insight into the altered methylation levels of watermelon cells in response to osmotic stress and suggest a new mechanism that how watermelon cells adapt to osmotic stress.